The Gollywhopper Games - Feldman, Jody.; Jamieson, Victoria (New York : Greenwillow Books, 2009)
Gil Goodson competes against many other children at puzzles, stunts, and more in hopes of a fresh start for his family, which has been ostracized since his father was falsely accused of embezzling from the local toy company.
Reprint. Originally published: c2008.
Keywords: Contests -- Fiction; Games -- Fiction; Puzzles -- Fiction; Conduct of life -- Fiction; Toy making -- Fiction